Challenges and Recent Progress on Silicon‐Based Anode Materials for Next‐Generation Lithium‐Ion Batteries. Issue 6 (19th June 2021) - Zhang, Chengzhi; Wang, Fei; Han, Jian; Bai, Shuo; Tan, Jun; Liu, Jinshui; Li, Feng
Abstract : Silicon-Based Anode Materials The development of long‐endurance and fast‐charging lithium‐ion batteries (LIBs) are important in electric vehicles. Silicon‐based anode materials have attracted much attention because of their ultrahigh capacity and suitable voltage platform and have been developed for the next generation of LIBs. In article number 2100009, Jun Tan, Feng Li, and co‐workers summarize the recent development of silicon‐based anode materials, in which the challenges, strategies and practical applications of silicon‐based materials are introduced. The focus is on combining with advanced structure, binders, electrolyte, prelithiation strategies and Si/graphite design to meet commercialization requirements.